Relationship between types, prevalence and common intensity of injuries with selected anthropometric properties with emphases of game's position among female elite volleyball players - Sharareh, S.; Sadeghi, H.; Amirtash, A. (European Journal of Experimental Biology, 2013)
The purpose of this research, show the relationship between the types, prevalence, and intensity of injuries common with selected anthropometric properties of elite women volleyball players playing in each of the posts. Methodology: 79 elite women volleyball players (mean 24.42% years old and with the 8.66% years sports history) in Iran`s super League in 1390, as a subjects of this research were completed the Personal Information Questionnaire Injuries reported to Australian Standard Questionnaire and Some anthropometric properties were measured. Using Descriptive statistics( mean, standard deviation, frequency percentage) to classify information and to determine the relationship between type, prevalence, and intensity of common injuries with game's position chi-square test, with a selection of anthropometric properties Pearson correlation coefficients and weighted regression coefficients were used. Results: This research showed 0.49% injuries per year, 1.46% per 1000 hours of training. Regardless of the game`s position, sprain (18.25%), ankle (25.26%) and severe injuries (45.26%), respectively are the most common type of injuries, anatomical spots and intensity of injuries. Discussion and Conclusion: Weighted regression coefficient showed the common injuries of volleyball like (sprains, dislocation of joint, bone fractures, chronic tendon,...) Have significant relationship with length and volume some of the limbs and diameters ofjoint. There is a significant relationship between some of environmental properties (torso circumference at hip, maximum arm circumference,.), seated vertical height and knee width with prevalence of injuries. Have significant relationship between weight, seated vertical height, torso circumference at hip, shank length and knee width with the intensity of injuries and length some of anthropometric properties and environmental properties with anatomical position of injuries including knee, shank, ankle, hip, finger, wrist, elbow and arm of elite woman volleyball players. According to the results, we can say that sprains, chronic tendon injury, inflammation and Swelling and anatomical parts ankles, knees, fingers are the most common type of injuries and anatomic parts injuries.